The impacts of shoulder position sense, vision, racket weight, and gender on racket positioning accuracy in tennis players - Collins, K.; Young, S.; Hung, Y.-J. (International Journal of Exercise Science, 2020)
Repetitive loading to the shoulder joint can compromise shoulder position sense, which may further contribute to injuries and performance deficits. The first goal of the study was to examine the correlation between shoulder position sense and racket positioning accuracy. The second goal of the study was to examine the impact of visual feedback, racket weight, and gender on racket positioning accuracy in tennis players. Fifty-eight tennis players participated in the study. Active shoulder position sense was examined in 3 abduction (45°, 90°, 135°) and 2 external rotation (45°, 90°) angles. For racket positioning accuracy, participants went through a tennis swing and had the center of the racket touch the ball with full or peripheral vision, and with normal or added (0.6 oz.) racket weight. Low correlation (Pearson`s r: from 012 to .381) was found between shoulder position sense and racket positioning accuracy. Shoulder position sense varied among different target angles (p < .001) and the variation was similar between genders (p = .123). Subjects performed better with full vision than with peripheral vision in both racket weight conditions (p < .001). However, racket weight (p = 1.000 for peripheral and p = .362 for full vision) and gender (p = .380) had no impact on racket positioning accuracy. Although the shoulder joint is part of the upper limb kinematic chain, shoulder position sense integrity may not have a direct impact on end-point racket positioning accuracy. Through motor learning, tennis players may have learned to coordinate all upper limb joints and muscles to achieve desired racket positioning accuracy.